A comparison of a simplified cupric oxide oxidation HPLC method with the traditional GC‐MS method for characterization of lignin phenolics in environmental samples. (28th January 2015) - Sun, Luni; Spencer, Robert G. M.; Hernes, Peter J.; Dyda, Rachael Y.; Mopper, Kenneth
Abstract: A simplified method to characterize the lignin phenolic composition of environmental samples using alkaline CuO oxidation, solid‐phase extraction (SPE), and high performance liquid chromatography (HPLC) is described. Samples were oxidatively hydrolyzed in inexpensive, commercially available Teflon vials rather than expensive high‐pressure Teflon‐lined reaction vessels. We used milder hydrolysis conditions than conventionally used to avoid "over‐oxidation." The monomeric lignin phenols released were extracted by SPE rather than liquid–liquid extraction and analyzed by reverse phase HPLC with ultraviolet (UV)‐visible diode array detection. Recoveries were 88% ± 6% for the overall procedure. The lignin phenolic composition of a wide variety of samples including plant tissues, isolated humic substances, soils, sediments, and freshwater dissolved organic matter are presented and compared with the conventional high pressure reaction vessel gas chromatography–mass spectrometry (GC‐MS) method. The agreement was generally good; the mean difference of nine diverse samples for a total of eight oxidation products was 4.5% with a relative standard deviation (RSD) of 23%. The advantages of this simplified method include no lengthy clean‐up and derivatization steps, no specialized reaction equipment, increased sample throughput, amenability to compound‐specific isotope analyses, and lower cost.